Asymmetries in the labor demand in Pakistan: estimating own and cross wage elasticities using frictional probit model - Khan, Muhammad Zaheer; Said, Rusmawati; Hafeez, Amtul; Maqsood, Naila; Qadir, Farheen (Economic Laboratory Transition Research Podgorica, 2022)
The objective of this study is to estimate asymmetries in the labor demand across industrial sectors in Pakistan and determine whether the behavioral economic explanation can be used for the labor demand structure and low employment generation in the country. This is done by estimating own and cross-wage elasticities of labor demand for workers categories in 3 different skill levels. Frictional panel Probit estimates indicate that the labor demand structure and low employment generation can be explained in terms of endowment effect and risk averting behavior of the country's industrial sectors.